Persepsi Kelas Pekerja tentang Korupsi (Studi pada Pekerja Sektor Formal dan Nonformal Malang Raya Provinsi Jawa Timur) - Hakim, Abdul; Setyowati, Endah (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2025)
The purpose of this study is to explain the perceptions of the working class, both in the formal and non-formal sectors, about the forms of corruption, and to what extent is the significance of differences in personal characteristics and job characteristics on the perceptions of the working class about the forms of corruption. This research uses a survey method to explain the perceptions of respondents in terms of their attitudes, values and beliefs on the phenomenon of corruption, through sampling of those who work in both the formal and informal sectors in Malang Raya. of this study consisted of 140 respondents. The sampling techniques used were cluster sampling and convenience sampling. This research uses questionnaires, interviews and secondary data. The data were analyzed using cross tabulation method, also known as Lazarsfeld technique. The results showed: (1). The level of knowledge or understanding of the respondents on attitudes and behaviors classified as corruption is still relatively low (2). There are three reasons that cause corruption, namely First, corruption occurs due to economic reasons, political factors, and social factors. The implication of this research is that it takes exemplary apparatus, especially from law enforcers in sentencing corruptors, so that it can be an example for the community and create a deterrent effect for corruptors.